2019
DOI: 10.1503/cmaj.181613
|View full text |Cite
|
Sign up to set email alerts
|

Early introduction of infant-safe peanut protein to reduce the risk of peanut allergy

Abstract: Infants who are fed peanut protein regularly have a lower risk of peanut allergy A randomized controlled trial that included 640 infants younger than 11 months with either egg allergy or moderate-severe atopic dermatitis found that 3.2% of children in the treatment group, who ate 2 g of peanut butter 3 times per week, developed peanut allergy after 5 years compared with 17.2% of children in the avoidance group (p < 0.001). 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We read with interest the article by Kalaichandran and colleagues 1 about early introduction of allergenic solids. We appreciate this focus, as it has been shown that early introduction of both peanut and cooked egg significantly reduce the risk of peanut and egg allergy, respectively.…”
Section: Pre-emptive Screening For Peanut Allergy Before Peanut Ingestion In Infants Is Not Standard Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Kalaichandran and colleagues 1 about early introduction of allergenic solids. We appreciate this focus, as it has been shown that early introduction of both peanut and cooked egg significantly reduce the risk of peanut and egg allergy, respectively.…”
Section: Pre-emptive Screening For Peanut Allergy Before Peanut Ingestion In Infants Is Not Standard Of Carementioning
confidence: 99%
“…Although Kalaichandran and colleagues suggested specific amounts of peanut ingestion, 1 to date there are inconclusive data regarding the exact amount and periodicity of peanut protein ingestion required to prevent peanut allergy. The LEAP study used a protocol of 6 g of peanut protein per week distributed over 3 or more meals, 2 but this has never been replicated, and to date, no study has tested whether a smaller amount would give the same protection.…”
Section: Pre-emptive Screening For Peanut Allergy Before Peanut Ingestion In Infants Is Not Standard Of Carementioning
confidence: 99%